Manejo de Balfourodendron riedelianum (Engl.) Engl. em formações secundárias: potencialidades e limitações - Lanzarin, Karina (2020)
Balfourodendron riedelianum (pau-marfim) is one of the most important commercial timber species in the South Region, recommended under the Project for the Future Project of the Ministry of the Environment, which encourages its research and sustainable use. Given this scenario, the present study aimed to verify the potential and limitations of the use of the species B. riedelianum in secondary forests aiming at its sustainable management. Also, it had as specific objectives: to characterize the horizontal structure and the successional stage of a fragment of Seasonal Deciduous Forest and to verify the growth potential of trees with characteristics of interest for the mechanical transformation of B. riedelianum wood in litholic neossols. Analyze under what conditions the natural regeneration of B. riedelianum is established and its possible restrictions; to verify the capacity of development of the natural regeneration of B. riedelianum in high densities and to identify dimensional patterns of the saplings; and, to analyze the height and phytosanitary conditions of B. rielianum saplings concerning the attack of herbivorous insects and environmental factors that can contribute to this. In a fragment of Deciduous Seasonal Forest with unique characteristics and soils of the type Neosol litolic, located in Pinhal Grande, RS, we sought to investigate the structure and composition of tree species and the diametric and cross-sectional growth of B. riedelianum. In a sample of 2.1 ha, were measured all adult trees with CAP ≥30 cm, and was calculated their horizontal structure. For growth analysis, were selected 12 trees with satisfactory silvicultural characteristics and were removed two wood cores at 1.30 m, using an increment borer. The annual periodic increments in diameter (IPAd) and transversal area (IPAg) for the last five years were calculated. The luminosity conditions and possible restrictions on the establishment and development of regeneration of B. riedelianum were investigated. In the forest, through walking, the presence of regenerating and diaspores dispersed on the ground was observed. In two gaps (Gap 1 and 2) a census of the saplings was performed, and the height of all plants of the species was measured. Subsequently, 71 individuals were sampled and were measured their crown diameter, leaf length, and branch height when present. Furthermore, the health of the saplings related to herbivory by arthropods, and factors that may contribute to this was analyzed. The plants were analyzed visually for apparent herbivory symptoms. In the crown of the saplings, arthropods were captured with an entomological net and later identified in the laboratory. The forest is in an advanced stage of succession, and B. riedelianum is one of the most important species in the community. The average IPAd of trees of the species was 0.67 cm/year, reaching up to 1.0 cm/year. The IPAg can achieve values of up to 81.57 cm² / year. The natural regeneration of B. riedelianum is preferentially established in gaps, has the capacity to develop in high density and to sprout, presenting high morphological plasticity. However, it does not develop in places with herbivorous domestic animals or places dominated by vines. The species is attacked by the psilid Leuronota cf. esenbeckiae, the first report of the presence of the insect in this species and in Brazil. Apparently, the damage caused by herbivory does not affect the height of the saplings, and the number of species does not contribute to a lower incidence of attack.